Народжуваність в Україні: вплив сучасних тенденцій на перспективи формування та майбутні характеристики людського капіталу - Мельничук, Д.П. (Інститут демографії та соціальних досліджень НАН України, 2010)
У статті охарактеризовано проблеми активізації репродуктивної поведінки населення, а також проаналізовано вплив динаміки народжуваності в Україні на перспективи формування її людського капіталу. В статье охарактеризованы проблемы активизации репродуктивного поведения населения, а также проанализировано влияние динамики рождаемости в Украине на перспективы формирования ее человеческого капитала. Problems of activation of reproductive behavior of the population have been characterized in the article as well as the influence of the birth rate dynamics in Ukraine on the perspectives of its human capital formation has been analyzed. On the basis of analyzing the statistical information and data interpretation got in the result of inquiries of the people of young reproductive age there have been made the conclusions concerning the conditionality of the dynamics of the reproduction of population in Ukraine by the level of socio-economic development of the state, the interconnection of the reproductive preferences of youth with the mentality stereotypes prevailing in the society has been analyzed as well as the specific of the motivation mechanism of the reproductive activity of the population has been specified in the article.